Risk factors for postoperative thrombotic complications after meningioma resection: a retrospective single-center study in China - Yingying Kong; Beibei Jin; Yijie Zhang; Jianhai Long (Frontiers in Neurology)
ObjectiveTo explore the incidence and risk factors for deep vein thrombosis (DVT) and pulmonary embolism (PE) following surgical intervention for meningioma.MethodsIn this retrospective, observational study, we enrolled 9,067 patients with histologically confirmed meningiomas who underwent surgical resection at our institution between January 2019 and June 2024. Demographic data (including gender, age, and geographic region) and information on comorbidity, and postoperative complications were documented and analyzed. The incidences of postoperative DVT and PE were also recorded. Risk factors for DVT and PE were identified using univariate and multivariate logistic regression analyses and restricted cubic splines.ResultsAmong the 9,067 patients who underwent meningioma surgery, 766 (8.4%) developed deep venous thrombosis (DVT) and 32 (0.35%) developed pulmonary embolism (PE). The mean age for patients with DVT was 59.39 ± 9.85 years, and for those with PE, it was 62.22 ± 9.86 years, both significantly higher than the overall patient population (p < 0.001). Geographically, the highest incidences of DVT and PE were found in Northeast, North, and East China, with provinces such as Hebei, Shandong, and Inner Mongolia reporting the highest rates. Associated risk factors for DVT included advanced age, asthma, heart failure, hypertension, and pneumonia. The associated risk factors for PE were age, DVT, pneumonia, and renal insufficiency. Multivariate analysis identified age, intracerebral hemorrhage (ICH), atrial fibrillation, heart failure, hyperlipidemia, varicose veins, hypothyroidism, hypoproteinemia, pneumonia, anemia, central nervous system infection as significant predictors for DVT, and age (OR: 1.05; 95% CI: 1.01–1.09), pneumonia (OR: 3.60; 95% CI: 1.65–7.85), and SDVT (OR: 15.88; 95% CI: 6.94–36.35) for PE. Nomogram models demonstrated strong predictive performance, with ROC values of 0.754 for DVT and 0.886 for PE.ConclusionThe incidences of DVT and PE following meningioma surgery were 8.4 and 0.35%, respectively. Age, comorbidities, and postoperative complications significantly influence the risk of these thromboembolic events. The study highlights the need for early identification and tailored prevention strategies, and the developed predictive models offer useful tools for clinical decision-making. However, the models’ overestimation of risk warrants further refinement to enhance their clinical applicability.